Emerging Trends in the Epidemiology of West Nile and Usutu Virus Infections in Southern Europe - Vilibic-Cavlek, Tatjana; Savic, Vladimir; Petrovic, Tamas; Toplak, Ivan; Barbic, Ljubo; Petric, Dusan; Tabain, Irena; Hrnjakovic-Cvjetkovic, Ivana; Bogdanic, Maja; Klobucar, Ana; Mrzljak, Anna; Stevanovic, Vladimir; et al. (Frontiers in Veterinary Science, 2019)
The epidemiology of West Nile (WNV) and Usutu virus (USUV) has changed dramatically over the past two decades. After 1999, WNV outbreaks were continuously detected with expanding area of its circulation in many Southern European countries. After the emergence in Italy (1996), USUV has spread to other countries causing mortality in several bird species. In 2009, USUV seroconversion in horses was reported in Italy. Co-circulation of both viruses was detected in humans, horses and birds. The main vector of WNV and USUV in Europe is Culex pipiens, however, both viruses were found in different native Culex mosquito species (Cx. modestus, Cx. perexiguus). Experimental competence to transmit the WNV was also proven for native and invasive mosquitoes of Aedes and Culex genera (Ae. albopictus, Ae. detritus, Cx. torrentium). Recently, Ae. albopictus and Ae. japonicus naturally-infected with USUV were reported. While neuroinvasive human WNV infections are well documented, USUV infections are sporadically detected. However, there is an increasing evidence of a role of USUV in human disease. Seroepidemiological studies showed that USUV circulation is more common than that of WNV in some endemic regions. Recent data showed that WNV strains detected in humans, horses, birds and mosquitoes mainly belong to lineage 2. In addition to European USUV lineages, some reports indicate the presence of African USUV lineages as well. The trends in WNV/USUV spreading are likely to continue in future years. This mini-review provides an update in the epidemiology/molecular epidemiology of WNV/USUV infections in Southern Europe in the multidisciplinary "One Health" context.